Large values of hydraulic roughness in subglacial conduits during conduit enlargement: Implications for modeling conduit evolution - Gulley, J. D.; Spellman, P.; Covington, M. D.; Martin, J. B.; Benn, D. I.; Catania, G. (Earth Surface Processes and Landforms, 2014)
Hydraulic roughness accounts for energy dissipated as heat and should exert an important control on rates of subglacial conduit enlargement by melting. Few studies, however, have quantified how subglacial conduit roughness evolves over time or how that evolution affects models of conduit enlargement. To address this knowledge gap, we calculated values for two roughness parameters, the Darcy-Weisbach friction factor (f) and the Manning roughness coefficient (n), using dye tracing data from a mapped subglacial conduit at Rieperbreen, Svalbard. Values of f and n calculated from dye traces were compared with values of f and n calculated from commonly used relationships between surface roughness heights and conduit hydraulic diameters. Roughness values calculated from dye tracing ranged from 75-0.97 for f and from 0.68-0.09 s m-1/3 for n. Equations that calculate roughness parameters from surface roughness heights underpredicted values of f by as much as a factor of 326 and values of n by a factor of 17 relative to values obtained from the dye tracing study. We argue these large underpredictions occur because relative roughness in subglacial conduits during the early stages of conduit enlargement exceeds the 5% range of relative roughness that can be used to directly relate values of f and n to flow depth and surface roughness heights. Simple conduit hydrological models presented here show how parameterization of roughness impacts models of conduit discharge and enlargement rate. We used relationships between conduit relative roughness and values of f and n calculated from our dye tracing study to parameterize a model of conduit enlargement. Assuming a fixed hydraulic gradient of 0.01 and ignoring creep closure, it took conduits 9.25 days to enlarge from a diameter of 0.44 m to 3 m, which was 6-7-fold longer than using common roughness parameterizations.